At-Tafkīr al-‘Ulyā HOTS Fī Ta’līm al-Lughah al-Arabiyyah Fī Tarqiyati Mahārah al-Kalām - Muhtarom, Muhammad Ikbal; Tohri, Muhammad; Satriawan, Satriawan (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2024)
Purpose—This study aims to examine the relationship between the implementation of higher-order thinking Skills (HOTS) and the success in enhancing speaking skills, focusing on social contexts and practical applications. It also seeks to identify the challenges encountered in Arabic language learning and the impact of HOTS implementation on improving students' ability to engage and communicate effectively at Pondok Pesantren Nurul Qur’an Al-Aziziyah. Design/Methodology/Approach - This study employs a descriptive qualitative method with data collection through observation, interviews, and documentation to examine the implementation of higher-order thinking Skills (HOTS) in Arabic language learning at Pondok Pesantren Nurul Qur’an Al-Aziziyah. The data collected are analyzed using thematic analysis, where emerging patterns or themes are linked to HOTS theory to provide a deeper understanding of the impact of HOTS implementation on improving students' speaking skills. The findings from this analysis will reveal the challenges, successes, and contributions of HOTS in Arabic language learning at the pesantren. Findings: The findings indicate that the implementation of HOTS in Arabic language learning to enhance speaking skills among students (santri) at Pondok Pesantren Nurul Qur’an Al-Aziziyah is carried out through systematic steps involving analysis, evaluation, and creativity. However, the challenges faced by the students primarily revolve around their motivation and mental state, including feelings of embarrassment, fear of making mistakes, lack of motivation, and the students' desire to learn Arabic and apply it in their daily lives. Research Limitation/Implications - The limitation of this research lies in its narrow focus solely on Pondok Pesantren Nurul Qur’an Al-Aziziyah, which may limit the generalizability of the findings to other educational institutions. Additionally, the depiction of challenges students face is based on their perceptions and experiences, potentially influencing the objectivity of the research outcomes.